2010
DOI: 10.4236/health.2010.29163
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character as predictor of health related quality of life after metacarpophalangeal joint arthroplasty ——Personality and MCP joint arthroplasty outcome

Abstract: Purpose: To evaluate personality characteris- tics’ impact upon outcome after silicone-based MP arthroplasty in RA patients. Methods: 40 RA patients who had undergone operations on their MP joints were investigated in a one-year fol- low-up. Objective measurement to assess grip strength and active range of motion—Paper- pencil-tests to assess pain during activity and at rest performance, QoL, and personality. Results: Significant improvement was observed in func- tion and pain related scores except for the pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…Our study has investigated the personality profile of the two major types of persistent pain (neuropathic and nociceptive), but it is important to acknowledge the existence of two minor pain types, inflammatory and dysfunctional, to identify a mutual personality profile of high Harm Avoidance and low Self‐Directedness independent of chronic pain type. Indeed, evidence is emerging that both inflammatory and dysfunctional pain share the same personality profile of high levels in Harm Avoidance and low levels in Self‐Directedness . Furthermore, in alignment with our study on ongoing orofacial pain, other investigations revealed that multiple chronic pain disorders such as migraine, tension‐type headache, nonspecific musculoskeletal disorders, radiculopathies, peripheral neuropathies, osteoarthritis, back, leg, neck, and arm pain, and abdominal pain disorders exhibit the same personality profile of high levels in Harm Avoidance and low levels in Self‐Directedness .…”
Section: Discussionsupporting
confidence: 86%
“…Our study has investigated the personality profile of the two major types of persistent pain (neuropathic and nociceptive), but it is important to acknowledge the existence of two minor pain types, inflammatory and dysfunctional, to identify a mutual personality profile of high Harm Avoidance and low Self‐Directedness independent of chronic pain type. Indeed, evidence is emerging that both inflammatory and dysfunctional pain share the same personality profile of high levels in Harm Avoidance and low levels in Self‐Directedness . Furthermore, in alignment with our study on ongoing orofacial pain, other investigations revealed that multiple chronic pain disorders such as migraine, tension‐type headache, nonspecific musculoskeletal disorders, radiculopathies, peripheral neuropathies, osteoarthritis, back, leg, neck, and arm pain, and abdominal pain disorders exhibit the same personality profile of high levels in Harm Avoidance and low levels in Self‐Directedness .…”
Section: Discussionsupporting
confidence: 86%